Knowledge of Health Insurance Program, Utilization, and Service Satisfaction among Insured in Suryabinayak Municipality, Nepal - Bhatt, Khem Raj; Aryal, Bhagwan; Khanal, Kalpana; Adhikari, Anup (Shiksha Shastra Saurabh, 2024)
The health insurance program is a social protection and health security program of the Government of Nepal that aims to enable its citizens to access quality healthcare services without placing a financial burden on them. Health insurance is essential for reducing financial barriers to healthcare and ensuring equitable access to health services. This study aimed to assess knowledge of the health insurance program, its utilization practice, and satisfaction with the service among the locals of Suryabinayak Municipality, Bhaktapur District, Nepal. A descriptive cross-sectional study used a structured questionnaire to collect data from 422 households. There was a high level of awareness (73.9%) and service utilization (38.4% using services frequently), with an 86% satisfaction rate among users. However, significant gaps remain in knowledge about specific benefits and access to emergency services, as well as issues with medication availability. Additionally, 7.1% of respondents experienced delays in renewal due to a lack of medicine. Health-insured people had a high level of awareness about the health insurance program, however, they had knowledge gaps in various aspects of the policy. Access to emergency care and essential medications remained questionable, which demanded targeted outreach and educational initiatives.